2022
DOI: 10.3390/su14084836
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Shock, Behavior, and Knowledge on the Financial Fragility of Single Youth

Abstract: Financial fragility is an important issue in the well-being of individuals. Previous studies have shown that many young people are vulnerable to financial fragility. To add value to previous findings, the issue of financial fragility was focused on single youths in the middle-income group (M40) in urban areas. The objective of the study was to determine the factors influencing the financial fragility of single youth (M40) in urban areas. A quantitative approach using a survey method was applied. The study’s sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Financial vulnerability is an important research perspective for analyzing the wellbeing of farmers (Zhang et al, 2020;Ramli et al, 2022). In the context of the Chinese government's vigorous efforts to reform the farmland ownership system and promote farmland circulation, this paper has systematically investigated the direct and indirect effects of farmland circulation on the financial vulnerability of farmers.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial vulnerability is an important research perspective for analyzing the wellbeing of farmers (Zhang et al, 2020;Ramli et al, 2022). In the context of the Chinese government's vigorous efforts to reform the farmland ownership system and promote farmland circulation, this paper has systematically investigated the direct and indirect effects of farmland circulation on the financial vulnerability of farmers.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Some scholars have found that there are multiple factors affecting household financial vulnerability. In addition to education (Anderloni et al, 2012;Ali et al, 2020), financial shock (Ramli et al, 2022), financial literacy Chhatwani and Mishra, 2021;Seldal and Nyhus, 2022), the use of digital payment technologies (Seldal and Nyhus, 2022), household assets, and the way they are allocated are also key factors influencing household financial vulnerability (Yusof et al, 2015;Consumer Financial Protection Bureau, 2022). As important assets owned by farming households (Li et al, 2022), farmland, as well as the livelihood strategies for its circulation, inevitably has important implications for the livelihood outcome of household financial vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Financial knowledge is an integral dimension of financial literacy in which people are considered financially literate when they can apply their financial knowledge to make financial decisions (Huston, 2010). Financial knowledge generally represents theoretical and practical understanding of financial concepts and facts, which is linked to the knowledge of financial products and its underlying principles (Forster et al, 2017), savings (Kim & Yuh, 2018), spending and indebtedness (Ramli et al, 2022), financial planning (Weisfeld-Spolter et al, 2018), retirement related financial planning (Noar, 2018), income earning, purchasing, protecting and insuring (Walstad & Rebeck, 2017) and debt management (Lusardi & Tufano, 2015). Financial knowledge can be defined as individual's understanding of important concepts related to personal finance (Robb & Sharpe, 2009), as well as the use of this understanding to solve financial problems (Swiecka, 2019).…”
Section: Conceptualizing Islamic Financial Knowledgementioning
confidence: 99%
“…Financial fragility is used to describe the individuals' and/or households' incapacity to cope with financial shocks and unexpected expenses (Clark & Mitchell, 2022). Ex-amples of such shocks is a decrease in working hours and salaries, job losses, changes in loan interest rates or stock markets and also physical disability, divorce, or death, (Ramli et al, 2022). The importance of financial fragility stems from the fact that it reduces or eliminates one's income and can lead to many adverse consequences in the end, such as an increase in debt, poverty, and subsequent bankruptcy (Chhatwani & Mishra, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of financial fragility stems from the fact that it reduces or eliminates one's income and can lead to many adverse consequences in the end, such as an increase in debt, poverty, and subsequent bankruptcy (Chhatwani & Mishra, 2021). Financial fragility not only hurts individuals' well-being and the well-being of their families, but it can produce an opposing effect on society and the macroeconomics of the whole country (Ramli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%